2017
DOI: 10.1021/acsnano.7b07504
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning of Atomically Resolved Scanning Transmission Electron Microscopy Images: Chemical Identification and Tracking Local Transformations

Abstract: Abstract:Recent advances in scanning transmission electron and scanning probe microscopies have opened exciting opportunities in probing the materials structural parameters and various functional properties in real space with angstrom-level precision. This progress has been accompanied by an exponential increase in the size and quality of datasets produced by microscopic and spectroscopic experimental techniques. These developments necessitate adequate methods for extracting relevant physical and chemical info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
315
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(319 citation statements)
references
References 44 publications
(77 reference statements)
2
315
0
2
Order By: Relevance
“…[17] Kirschner and Hillebrand have published a method for predicting defocus and sample thickness, [18] and Meyer and Heindl have used neural networks to reconstruct the exit wave function from off-axis electron holograms. [19] Whereas deep learning methods have recently been proposed to analyze scanning TEM (STEM) images, [20] but have, to our knowledge, not yet been used to analyze the atomic structure in HRTEM images. In this article, we describe a convolutional neural network (CNN) based method for classifying atomic structures in TEM, and demonstrate that it can be applied to single layers of graphene, as well as to supported metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Kirschner and Hillebrand have published a method for predicting defocus and sample thickness, [18] and Meyer and Heindl have used neural networks to reconstruct the exit wave function from off-axis electron holograms. [19] Whereas deep learning methods have recently been proposed to analyze scanning TEM (STEM) images, [20] but have, to our knowledge, not yet been used to analyze the atomic structure in HRTEM images. In this article, we describe a convolutional neural network (CNN) based method for classifying atomic structures in TEM, and demonstrate that it can be applied to single layers of graphene, as well as to supported metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…E, Tracking the defect dynamics and symmetry conversion of a Si dopant in a graphene matrix using the neural network. A‐E, Reproduced with permission from Reference Copyright 2017, American Chemical Society…”
Section: Structure Identification Via Machine Learningmentioning
confidence: 99%
“…However, the construction of the simulated images relies on prior knowledge. In the case of point defect identification, Ziatdinov generalized dopants with higher atomic number and vacancies to the ideas of protrusion and depression . The model is only fitted and validated by simulated data on 2D materials.…”
Section: Structure Identification Via Machine Learningmentioning
confidence: 99%
“…DeCost and Holm 22 used convolutional neural networks (CNNs) to predict properties of materials samples based on their microstructures. Ziatdinov et al 23 automatically identified defects in atomic-scale microscopy data with deep learning. Xu and LeBeau 24 employed CNNs to dramatically accelerate the process of analyzing electron beam diffraction patterns.…”
Section: Enhanced or Accelerated Characterizationmentioning
confidence: 99%